Endothelial Notch signaling controls insulin transport in muscle - Safatul Hasan, Sana; Jabs, Markus; Taylor, Jacqueline; Wiedmann, Lena; Leibing, Thomas; Nordström, Viola; Federico, Giuseppina; Roma, Leticia P; Carlein, Christopher; Wolff, Gretchen; Ekim-Üstünel, Bilgen; Brune, Maik; et al. (EMBO molecular medicine, 2020)
The role of the endothelium is not just limited to acting as an inert barrier for facilitating blood transport. Endothelial cells (ECs), through expression of a repertoire of angiocrine molecules, regulate metabolic demands in an organ-specific manner. Insulin flux across the endothelium to muscle cells is a rate-limiting process influencing insulin-mediated lowering of blood glucose. Here, we demonstrate that Notch signaling in ECs regulates insulin transport to muscle.
Gesehen am 08.04.2020